Species of the subtribes Arrenoseiina and Proprioseiopsina (Tribe Amblyseiini) and the tribe Typhloromipsini (Acari: Phytoseiidae) from sub-Saharan Africa - Moraes, G.J. de; Zannou, I.D.; Ueckermann, E.A.; Oliveira, A.; Hanna, R.; Yaninek, John S. (2007)
This is the fourth publication of a series to determine the phytoseiid mites of sub-Saharan Africa. Twenty-six phytoseiid species of the subtribes Arrenoseiina Chant & McMurtry (5 species) and Proprioseiopsina Chant & McMurtry (9 species), and tribe Typhlodromipsini Chant & McMurtry (12 species), are reported in this paper. They refer to all species of these taxa known to occur in sub-Saharan Africa. Eight of these species are described for the first time, 14 species are redescribed and 4 are not evaluated in this study. Most of those species were collected in cassava habitat in tropical Africa and in other habitats in South Africa. Keys are included to help in the separation of the species in each tribe or subtribe.